The secret language of girls - Dowell, Frances O'Roark. (New York : Aladdin Paperbacks, 2005)
Marylin and Kate have been friends since nursery school, but when Marylin becomes a middle school cheerleader and Kate begins to develop other interests, their relationship is put to the test.
"Aladdin fiction"--Cover.
Publisher's Weekly.
School Library Journal.
Wilson's Junior High School.
4.9
3-6
Keywords: Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction; Friendship -- Fiction; School stories